Clinical and Pathological Characteristics of High Grade Colorectal Adenocarcinoma at Hasanuddin University Hospital, Indonesia, 2015-2020 - Gusti Deasy W.A; Muhammad Husni Cangara; Andi Alfian Zainuddin; Djumadi Achmad; Syarifuddin Wahid; Upik Anderiani Miskad (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
Colorectal cancer is one of the most common cancers and the fourth leading cause of cancer-related death in the world. According to the type of histopathology, more than 90% of colorectal carcinomas are adenocarcinomas which are grouped into low grade and high grade based on their grading. Identification of characteristic groupings based on grading is still rarely done in Indonesia, especially in Makassar. This study aims to determine the clinical and pathological characteristics of high grade colorectal adenocarcinoma at Hasanuddin University Hospital, Makassar from January 2015 to December 2020. This study used a descriptive method. The sample used was a sample that was diagnosed histopathologically as high grade colorectal adenocarcinoma and met the inclusion criteria then selected by total sampling and also used data from medical records. The distribution of data in this study is classified based on age, gender, tumor location, clinical symptoms, and tumor stage. Descriptive statistical calculations were performed using SPSS 20 for Windows software. There were 98 samples, most of which were at the age of ?50 years, as many as 32 samples (32.7%) with man as many as 60 samples (61.2%). The most common location was in the rectum as many as 38 samples (38.8%) with the most clinical symptoms were bowel disorders as many as 68 samples (69.4%) and stage 3 was the most cases with 35 samples (35.7%).